SIMULTANITAS STRUKTUR KEPEMILIKAN, KEBIJAKAN DIVIDEN, DAN UTANG - Krisna Mutiara Wati (Fakultas Bisnis UKDW, 2012)
The purpose of this study is to examine the simultaneity of four financial variable, i.e. institutional ownership, managerial ownership, dividend policies, and Debt. This study analyzes a sample of IDX-listed manufacturing firms over the period 2006 – 2010. The coefficients of model are estimated using two stage least square model. The results show a number of important findings. Firstly, institutional ownership was determined simultaneously with managerial ownership, and the coefficient support agency hypothesis. Secondly, institutional ownership was determined simultaneously with dividend, but the coefficient does not support agency hypothesis. Thirdly, institutional ownership was not determined simultaneously with debt. Fourthly, dividend was determined simultaneously with dividend with debt.Keywords: ownership structure, dividend, debt